Efficacy of snap-needle patch therapy in pediatric epilepsy: a case study - Shi, Jia; Gong, Yu; Deng, Yuanyuan; Ma, Zhen; Xiao, ZiChun; Tan, HanYing; Qin, WeiLan (Frontiers in Human Neuroscience, 2025)
BackgroundsEpilepsy is a prevalent neurological disorder in early childhood, often characterized by genetic predisposition and diverse clinical manifestations. Benign epilepsy of childhood with central temporal spikes (BECTS) is the most common form of self-limited focal epilepsy (SeLFE) syndrome in children, accounting for approximately 6%–7% of all childhood epilepsy cases (Wirrell et al., 2011; Camfield et al., 1996). We report a case of a child who was treated with additional snap-needle for 3 months on top of poorly controlled oral medication alone, who stopped having seizures and gradually reduced the dose of oral medication and finally stopped, and was followed up for 1 year after stopping the medication without any recurrence.Case summaryA 10-years-old male had his first generalized tonic-clonic seizure (GTCS) at age 7 during nocturnal sleep. Following this event, the parents sought medical evaluation, and an electroencephalogram (EEG) showed abnormal wave patterns. Over the following 3 years, the child had 2–3 GTCS annually; despite multiple adjustments to antiepileptic drug (AED) therapy, GTCS frequency indicated disease progression. However, after starting snap-needle patch therapy [guided by Traditional Chinese Medicine (TCM) principles], the child remained seizure-free. Continuous monitoring has been conducted to date. We present this case of a pediatric patient with epilepsy: oral medication failed to control GTCS, but snap-needle patch therapy achieved successful seizure management, after which oral medication was discontinued.ConclusionAfter a systematic literature search, this study represents the first case report of BECTS treated with snap-needle therapy (needle size: 0.220 mm × 1.5 mm). In this case, the child’s GTCSs resolved following the addition of snap-needle therapy, and oral antiepileptic medication was gradually reduced to complete discontinuation; no seizure recurrence was observed within 1 year of follow-up. It is important to acknowledge that the contributions of medication adjustments and the self-limiting nature of BECTS cannot be ruled out in this case. However, based on the observations here, we propose the hypothesis that snap-needle intervention is likely associated with seizure remission. Although the mechanism underlying snap-needle therapy for BECTS remains unclear, the child achieved a QOLCE-16-C score of 98.4 at the end of treatment; during the 1-year follow-up, the number of nighttime sleep disruptions also decreased from 2 to 5 episodes per year to 0. These outcomes surpass those typically achievable through pharmacological intervention alone.